PENGARUH KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA PEGAWAI DI KANTOR CAMAT TELUKDALAM KABUPATEN NIAS SELATAN - Melvin Kristiani Duha (Jurnal Ilmiah Mahasiswa Nias Selatan, 2023)
The problem of this research is that some employees are still less skilled at work, lack of employee performance. The author aims to determine the effect of organizational commitment on employee job satisfaction in the Telukdalam sub-district office, South Nias Regency. The purpose of this study was to see how much influence organizational commitment has on employee job satisfaction in the Telukdalam District Office, South Nias Regency. This type of research is quantitative. The data source was obtained from 31 employees and casual daily workers. Based on the tcount value of Organizational Commitment of 6.976 with a significant level of 0.941 while the ttable value at alpha is 0.05 with degrees of freedom (df) n-k1 31-1-1 = 29 of 1.699. Based on the R2 value of 0.627, it means that the X variable has a 27% influence on Y while the remaining 0.73 or 73% is explained by other variables outside this model. Organizational commitment needs to be increased so that employees have satisfaction at work. The Head of the Telukdalam District Office, South Nias Regency, should have known in more detail about the importance of organizational commitment, in this case maintaining relationships with superiors, relationships with colleagues, and relationships with subordinates. So that it can increase employee job satisfaction and organizational goals can be achieved optimally.